The Prophylactic Effect of Eucheuma spinosum on Total Blood Cholesterol Levels in Rattus norvegicus Dexamethasone-Induced - Josefus Kristoforus Kresno Widjojo; Fitri Handajani; Duti Sriwati Aziz; Peppy Nawangsasy (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2023)
Hyperlipidemia is one of the main risk factors for heart disease caused by the formation of atherosclerosis. Eucheuma spinosum contains a natural antioxidant flavonoid, which has an antiatherogenic effect that can inhibit the formation of cholesterol in the liver so that it can prevent the development of atherosclerosis. This study aims to determine the effect of prophylactic administration of Eucheuma spinosum on the total cholesterol levels of Rattus novergicus induced by dexamethasone. This study was an experimental design with a post-test-only control group design. This study would use 24 white male Rattus norvegicus divided into three groups; a negative control group (K-) without treatment, a positive control group (K+) induced dexamethasone 8 mg/Kg BW on day 14 until day 20, treatment group (KP) given Eucheuma spinosum extract 200 mg/Kg BW on day 8 until day 20 as Prophylactic and on day 14 until day 20 induced dexamethasone 8 mg/Kg BW. After completing the treatment period, all groups were terminated and taken total calculation of cholesterol levels through the aorta of rats. Data was analyzed statistically computerized. The results of the study of total cholesterol levels that used Kruskal-Wallis test showed differences between groups (p<0.001). There was a decrease in total cholesterol levels in the treatment group (p<0.024) compared with the positive control group. The administration of Eucheuma spinosum extract as a prophylactic dose of 200 mg/Kg BW for 14 days could reduce the total cholesterol level of Rattus norvegicus induced by dexamethasone compared to those not given Eucheuma spinosum extract.